2015
DOI: 10.1007/s10803-015-2446-1
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report of Preliminary Outcomes of an Emotion Regulation Intervention for Children with Autism Spectrum Disorder

Abstract: Children with autism spectrum disorder (ASD) often present with comorbid psychopathology including problems with emotion regulation. The goal of the present research was to investigate the feasibility of a multicomponent manualized cognitive behavior therapy treatment program for improving emotion regulation in youth with ASD 8 to 12 years of age. Thirteen males and their parents participated in the intervention, reporting high satisfaction with the activities and program overall, and attending all sessions. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 39 publications
1
38
0
Order By: Relevance
“…The subscales of family involvement and affective strength both had moderate effect sizes, while the interpersonal strength was short of a moderate effect size, even though statistical significance was not reached. The findings were consistent with previous studies, where children's emotion regulation skills improved after receiving the CBT interventions (Scarpa & Reyes, 2011;Thomson et al, 2015). Further, Scarpa and Reyes (2011) found that the parents rated their children with a significantly higher level of confidence to handle negative emotions after intervention, similar to the increased intrapersonal strength measured by BERS.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The subscales of family involvement and affective strength both had moderate effect sizes, while the interpersonal strength was short of a moderate effect size, even though statistical significance was not reached. The findings were consistent with previous studies, where children's emotion regulation skills improved after receiving the CBT interventions (Scarpa & Reyes, 2011;Thomson et al, 2015). Further, Scarpa and Reyes (2011) found that the parents rated their children with a significantly higher level of confidence to handle negative emotions after intervention, similar to the increased intrapersonal strength measured by BERS.…”
Section: Discussionsupporting
confidence: 89%
“…Besides modifying the content to be developmentally appropriate, most CBT programs incorporate instructional strategies of applied behavior analysis (ABA) when working with individuals with ASD, such as assistive prompts and token economies (Lang et al, 2010). For example, Thomson, Riosa, and Weiss (2015) employed a CBT-based emotion regulation intervention for children with ASD with a token economy to promote and maintain motivation for children in the program. The parents reported a significant improvement in overall emotion regulation for their children, and the children reported decreased emotion dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from directly examining the relationships between ER and internalizing and externalizing problems, we can also infer the role that ER plays in the maintenance of these problems by studying the changes in symptoms post interventions that target ER. Although ER intervention research in ASD is still in its infancy, preliminary results from recent pilot studies are encouraging and indicate that ER intervention approaches including cognitive behavior therapy [Scarpa & Reyes, ; Thomson, Riosa, & Weiss, ] and mindfulness‐based intervention [Conner & White, 2017] are feasible and effective, and can improve emotional acceptance, impulse control, negative reactivity, and internalizing and externalizing symptoms in both children and young adults. Research in non‐ASD populations has also demonstrated the efficacy of ER intervention in reducing symptoms of mental health disorders [e.g., see Mennin & Fresco, ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, cognitive-behavioural interventions have been used to successfully decrease emotion regulation difficulties and increase coping skills in youth with ASD (e.g. Sofronoff et al 2007;Thomson et al 2015). Likewise, behavioural interventions, such as functional communication training (Carr and Durand 1985), have been shown to decrease a host of maladaptive behaviours by increasing desired ones, reflecting a mixed focus.…”
Section: Discussionmentioning
confidence: 99%